Diatom diversity patterns over the past c. 150 years across the conterminous United States of America: Identifying mechanisms behind beta diversity. Issue 11 (4th October 2017) - Winegardner, Amanda K.; Legendre, Pierre; Beisner, Beatrix E.; Gregory‐Eaves, Irene
Abstract: Aim: Understanding the magnitude and drivers of freshwater diversity over the last 150 years provides essential insights for developing scenarios of future change. Here, we quantify and identify drivers of spatial and temporal beta diversity in diatom assemblages between historical and modern times. Location: United States of America. Major Taxa Studied: Diatoms. Tim Period: pre‐AD 1850 and c. 2007. Methods: Using sedimentary genus‐level diatom data from 169 lakes and species‐level data for 52 lakes, we computed spatial beta diversity across all lakes and within ecoregions for 2007 and pre‐AD 1850 time points. We also computed local contributions to beta diversity (LCBD) and analysed them with respect to environmental variables. Total beta diversity was partitioned into replacement and abundance difference components to identify mechanisms possibly responsible for spatial beta at each time point. Temporal beta diversity indices (TBI) were also computed for each lake by comparing the diatom data of all lakes at the time points. TBIs were decomposed into taxon losses and gains to facilitate interpretation. TBIs and their components were related to contemporary land cover. Results: Temporal beta diversity varied significantly as a function of forest cover, with higher temporal beta in lakes from watersheds with contemporary lower forest cover. Spatial beta diversity was similar between the historical and 2007 time points. Lakes with substantial local contributions to beta diversity were differentiated by water quality and land cover variables at a local scale, but showed no systematic regional pattern. Main conclusions: Spatial beta diversity of diatoms across the U.S.A. does not appear to have changed between pre‐AD 1850 and 2007, suggesting that broad‐scale land use and hydrological alteration of the landscape has not homogenized these communities. Temporal beta diversity occurred through genus gains and losses and was significantly related to land cover in watersheds. These analyses, pairing spatial and temporal beta diversity, provide insight into the mechanisms maintaining diatom diversity.